Entry-Exit Timing and Profit Sharing - Michele Moretto; Sergio Pastorello (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1995)
We analyze the effects of two compound investment options, a shut down and a reopening option, on a Aoki's profit sharing firm organization. Whilst the introduction of a credible threat of shutting down weakens labour's position in the bargaining and favors the shareholders on profit sharing, the option to reopen the plant acts in the opposite direction, reducing the abandoning threat and reinforcing the workers' bargaining power. More specifically, as long as an increase in uncertainty leads to an increase in the benefit from reopening, and hence in the firm's market value, the overall result implies a weakening of the shut down threat and the profit distribution process becomes more favorable to workers.
Keywords: 330